Improved Lagrangean Decomposition: An Application to the Generalized Assignment Problem - Bárcia, Paulo (2019)
Recently two new ways of obtaining improved Lagrangean bounds have been suggested: Lagrangean decomposition and bound improving sequences. In this work we will obtain a Lagrangean approach combining the two ideas mentioned above. We provide theoretical results about the sharpness of the bounds obtained by the combined approach for the general case and an application to the generalized assignment problem. Computational experience is reported.